2000
DOI: 10.1093/jpepsy/25.1.23
|View full text |Cite
|
Sign up to set email alerts
|

Randomized, Controlled Trial of Behavior Therapy for Families of Adolescents With Insulin-Dependent Diabetes Mellitus

Abstract: BFST yielded some improvement in parent-adolescent relationships; its effects on diabetes outcomes depended on the adolescent's age and gender. Factors mediating the effectiveness of BFST must be clarified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
179
1
4

Year Published

2002
2002
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 252 publications
(185 citation statements)
references
References 23 publications
1
179
1
4
Order By: Relevance
“…The next most critical goal is the adaptation of established parenting education curricula, such as the Systematic Training for Effecting Parenting (STEP) program 23 and Raising an Emotionally Intelligent Child, 24 which are based on the concepts of parenting styles discussed earlier and into which could be integrated proven pediatric behavioral diabetes family-based interventions, such as Coping Skills Training, 25 Behavioral Family Systems Therapy, 26 and Family Teamwork. 27 For diabetes health care providers, the child development literature instructs us to help parents build, if necessary, a new parenting style specific to diabetes management.…”
Section: From Research To Practice / Children and Families Living Witmentioning
confidence: 99%
“…The next most critical goal is the adaptation of established parenting education curricula, such as the Systematic Training for Effecting Parenting (STEP) program 23 and Raising an Emotionally Intelligent Child, 24 which are based on the concepts of parenting styles discussed earlier and into which could be integrated proven pediatric behavioral diabetes family-based interventions, such as Coping Skills Training, 25 Behavioral Family Systems Therapy, 26 and Family Teamwork. 27 For diabetes health care providers, the child development literature instructs us to help parents build, if necessary, a new parenting style specific to diabetes management.…”
Section: From Research To Practice / Children and Families Living Witmentioning
confidence: 99%
“…BFST is a structured, manualized intervention that includes four primary components: problem-solving, communication skills, cognitive restructuring, and family systems interventions. BFST improves family communication and problem-solving when compared with standard medical care (11)(12)(13). A modified version, BFST for Diabetes (BFST-D), which specifically targets optimizing diabetes care, significantly improves glycemic control, treatment adherence, and diabetes-related family conflict among adolescents with type 1 diabetes (14,15).…”
mentioning
confidence: 99%
“…At 12 months, diabetes-specific family conflict was significantly improved compared to the control group. The experimental group showed improved treatment adherence compared with the control and education groups that both showed deteriorated adherence (Wysocki et al, 2000;Wysocki et al, 2001). When parental involvement decreases, which is frequent in early adolescence, the metabolic control tends to deteriorate.…”
Section: Coping Skills Training With Parents and Children Or Adolescentsmentioning
confidence: 87%
“…It has been shown that family interventions decrease parent-child conflicts about diabetes and improve metabolic control (Grey et al, 2003;Wysocki et al, 2000;Wysocki et al, 2001). One study that includes 119 families of adolescents with type 1 diabetes mellitus, assessed the effectiveness of an experimental group receiving Behavioral-Family Systems Therapy compared to both education and support groups in reducing parent-adolescent conflict in diabetes management.…”
Section: Coping Skills Training With Parents and Children Or Adolescentsmentioning
confidence: 99%